A rare case of Swyer syndrome from Pakistan in a young girl with primary amenorrhea and 46XY genotype - Inshal Jawed; Ayesha Azhar Javed; Syeda Alisha Johar; Daayl N Mirza; Ayesha A Abdani; Asad Ali Khan (Women's Health, 2023)
Swyer syndrome is a condition where individuals with a 46XY karyotype, typically associated with males, display complete gonadal dysgenesis and lack testicular differentiation. This results from a mutation in the SRY gene, which is essential for testis development. As a consequence, affected individuals who appear phenotypically female have male chromosomes but do not develop functional testes. As a result, there is an absence of testosterone that leads to lack of masculinization and the presence of female genitalia. This article describes a 20-year-old female from Pakistan who exhibited primary amenorrhea. On examination, she possessed a typical female physique but lacked breast growth and axillary hair. She had scant pubic hair with female-type external genitalia. The pelvic imaging showed a underdeveloped uterus, along with small ovaries and fallopian tubes. Her karyotype came out to be 46XY. The examination and radiological results indicated Swyer syndrome. During laparoscopy, the patient’s uterus was found to be infantile, while the fallopian tubes were healthy. Streak gonads were also present, and due to the risk of gonadoblastoma, they were surgically removed. Hormone replacement therapy was started to induce pubertal development and optimize bone mineral accumulation.